Sistem Informasi Pembayaran SPP Berbasis Web Pada SDIT Menggunakan Model RAD - Yesi Damaryanti; Eva Zuraidah (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
Tuition fee payments still often experience problems such as data collection and payment information processes which are done manually, conventionally, and not yet computerized, where recording reports still use ledgers, making work neglected and spending a lot of time and energy for the finance department in searching for student data and archiving it, currently There is a need for innovative use of technology in the world of education to assist financial administration in schools so that data collection and payment information processes run effectively and efficiently. This design aims to assist the finance department in recording tuition payments and as a means of informing parents/guardians about payments. The research method used is the RAD (Rapid Application Development) method and the programming language used is PHP, and Mysql as a web design medium and combines layout with programming languages. This application helps the finance department in recording tuition payments and summarizing data every month. Testing is carried out by testing the function of the code that is created and is functional by testing links, and existing menu buttons and ensuring that all parts have been tested. The development stage includes the needs analysis stage, design stage, implementation stage, and testing stage. The system designed by the tuition fee administration information website provides good results because the system runs as expected and can present student payment transaction data reports such as data management, announcement data, payment history data, payment transaction data, transaction report data, note printing data, and organize data. According to the white box test on administration, the SPP payment transaction report is effective and efficient because the test results prove that no errors were found